ADVANCING EDUCATIONAL EQUITY: THE ROLE OF GENERATIVE AI IN CREATING ACCESSIBLE AND INCLUSIVE HIGHER EDUCATION - Gaurav Krishan Ohri (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article explores the transformative role of generative AI in creating more accessible and inclusive higher education environments. It examines how AI technologies revolutionize educational accessibility through advanced language support, personalized learning systems, and comprehensive mental health services. The article investigates the implementation of AI-powered solutions across various domains, including communication tools, assessment methodologies, inclusive design practices, and student support systems. The article demonstrates how these technologies are breaking down traditional educational barriers, particularly for students with disabilities, non-native speakers, and those from underserved populations. Through analysis of recent implementations and research findings, the article highlights the significant improvements in student engagement, retention, and academic performance achieved through AI integration. Furthermore, it addresses the technical considerations, infrastructure requirements, and ethical guidelines for successfully deploying these technologies in educational settings. The findings suggest that AI-enhanced education systems play a crucial role in democratizing access to quality education while maintaining high privacy, security, and inclusivity standards.